An Evaluation of Readily Usable Automatic Video Shot Segmentation Techniques - Kishi, Rodrigo Mitsuo; Trojahn, Tiago Henrique; Goularte, Rudinei (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
Shot segmentation is a fundamental task in video systems, being a prior step to scene detection and summarization. Although the literature provides large number of automatic shot segmentation techniques, most of them cannot be easily used by researchers simply because they aren’t available to download, use legacy technology or are paid. This paper provide an evaluation of easily obtained video shot segmentation software in a benchmark composed by a set of movies and documentaries. Results, although may not be comparable to state-of-the-art, have significant meaning because these methods could be actually used by anyone.